The The maximum size of the Greater one-horned rhinoceros (rhinoceros unicornis) - Kees Rookmaaker (Pachyderm)
Data on the size of Rhinoceros unicornis individuals in the wild are only reported in rare cases, usually after the animal was killed or more recently during translocation exercises. In a survey of literature, records regarding body length, height at shoulder, girth and horn length have been collated and calculated in metric dimensions. The maximum figures are body length to 436 cm, height at shoulder to 206 cm, girth of body to 380 cm and horn length to 61 cm.